1995
DOI: 10.3102/01623737017003355
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Reports on Opportunity to Learn: Analyses of the 1993 California Learning Assessment System (CLAS)

Abstract: The California Learning Assessment System 1993 OTL Study allowed examination of the extent to which California public school mathematics teachers had been exposed to the practices consistent with those advocated in the California Curriculum Frameworks; the extent to which those teachers implemented these practices in their classrooms; and their impact on student performance in mathematics. The findings support the conclusion that curriculum and instruction that require higher level skills benefit students’ ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 7 publications
2
25
0
4
Order By: Relevance
“…Educators are generally expected to keep abreast of the important advances occurring in education including remaining current on the increasing amount of pedagogical and content area research. Studies have shown that teachers who participate in sustained professional development activities which are grounded in content-specific pedagogy linked to new curriculum they are learning to teach are likely to have better results for their students (Wiley & Yoon, 1995). A report by Wei, Darling-Hammond, Andree, Richardson, and Orphanos (2009) showed that states like North Carolina have posted largest student achievement gains in mathematics and reading scoring above the national average after introducing major changes which included teacher mentoring and ongoing professional development.…”
Section: Support For Teachers Of Stem Subjectsmentioning
confidence: 99%
“…Educators are generally expected to keep abreast of the important advances occurring in education including remaining current on the increasing amount of pedagogical and content area research. Studies have shown that teachers who participate in sustained professional development activities which are grounded in content-specific pedagogy linked to new curriculum they are learning to teach are likely to have better results for their students (Wiley & Yoon, 1995). A report by Wei, Darling-Hammond, Andree, Richardson, and Orphanos (2009) showed that states like North Carolina have posted largest student achievement gains in mathematics and reading scoring above the national average after introducing major changes which included teacher mentoring and ongoing professional development.…”
Section: Support For Teachers Of Stem Subjectsmentioning
confidence: 99%
“…27 Although we think better research on these issues is essential, we would be surprised if the direction of the effects we have found, and our model of causation, did not stand up in a more powerful design. Therefore, we think it would be wise for policymakers and practitioners to ground teachers' professional education more solidly in deeper knowledge of the student curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…The kind and quality of in-service professional development as well as pre-service education may make a difference in developing this knowledge. Several studies done by Cohen and Hill (1997); Wiley and Yoon (1995); Brown, Smith and Stein (1995) have found that higher levels of student achievement are associated with teachers' opportunities to participate in sustained professional development grounded in content-specific pedagogy linked to the new curriculum they are learning to teach. Furthermore, the results show positive correlations between the organizational culture, personal effectiveness and work-related stress in teachers.…”
Section: Discussionmentioning
confidence: 99%